Association Among End-Of-Life Discussions, Cancer Patients' Quality of Life at End of Life, and Bereaved Families' Mental Health. (September 2022) - Hayashi, Yoko; Sato, Kazuki; Ogawa, Masahiro; Taguchi, Yoshiro; Wakayama, Hisashi; Nishioka, Aya; Nakamura, Chikako; Murota, Kaoru; Sugimura, Ayumi; Ando, Shoko
End-of-life discussions are essential for patients with advanced cancer, but there is little evidence about whether these discussions affect general ward patients and family outcomes. We investigated the status of end-of-life discussions and associated factors and their effects on patients' quality of death and their families' mental health. Participants in this retrospective cross-sectional observational study were 119 bereaved family members. Data were collected through a survey that included questions on the timing of end-of-life discussions, quality of palliative care, quality of patient death, and depression and grief felt by the families. Approximately 64% of the bereaved family members participated in end-of-life discussions between the patient and the attending physician, and 55% of these discussions took place within a month before death. End-of-life discussions were associated with the patients' prognostic perception as "incurable, though there is hope for a cure" and "patients' experience with end-of-life discussions with family before cancer." There was a small decrease in depression and grief for families of patients who had end-of-life discussions. Those who did not have end-of-life discussions reported lower quality of end-of-life care.